Relationship between force-velocity profiles and 1,500-m ergometer performance in young rowers - Giroux, C.; Maciejewski, H.; Ben-Abdessamie, A.; Chorin, F.; Lardy, J.; Ratel, S.; Rahmani, A. (International Journal of Sports Medicine, 2015)
Rowing races require developing high level of force and power output at high contraction velocity. This study determined the force-velocity and power-velocity (F-P-V) profiles of lower and upper limbs of adolescent rowers and their relationships with a 1,500-m rowing ergometer performance. The power developed during the 1,500-m (P1500) was evaluated in fourteen national-level male rowers (age: 15.3±0.6 yrs). F-P-V profiles were assessed during bench pull (BP) and squat jump (SJ) exercises. The theoretical maximal values of force (F0), velocity (V0), power output (Pmax) and the F-V relationship slope (S FV ) were determined. The body mass (BM) influence on these relationships was considered using an allometric approach. F0 was 720±144 and 2146±405 N, V0 was 1.8±0.1 and 1.8±0.3 m·s-1, Pmax was 333±83 and 968±204 W and SFV was -391±54 and -1,200±260 N·s·m-1 for BP and SJ, respectively. Upper and lower limb F0 and Pmax were significantly related. P1500 was significantly (P<0.05) correlated to V0-BP, F0-BP, SFV-BP, Pmax-BP, F0-SJ and Pmax-SJ (r²=0.29 to 0.79). BM accounted for more than 90% of these relationships. Rowers` F-P-V profiles reflect adaptations to chronic rowing practice. F-P-V profiles and rowing performance correlations suggest that BP and SJ exercises are relevant to evaluate young rowers` explosive abilities.